CLINICAL AND SUBCLINICAL CHARACTERISTICS OF BREAST CANCER PATIENTS UNDERGOING TRASTUZUMAB TREATMENT (Tạp chí Y học Cộng đồng, 2022)
Objective: Describing the clinical and subclinical characteristics of the breast cancerpatient treated with Trastuzumab at Thong Nhat hospital.Subjects and methods: A retrospective study on 48 patients with breast cancer weretreated with Trastuzumab at Thong Nhat hospital.Results: Mean age: 48.4 ± 3.4 years old. The 45-60 age group accounted for thelargest proportion with 47.92%. Functional symptoms: the proportion of patients whoself-examined the tumor accounted for the highest rate with 64.58%. There were12.50% of patients with pain symptoms, 10.42% of patients with nipple discharge.Physical symptoms: tumor in the upper-external quadrant accounted for the largestpercentage with 58.33%. The average size of the tumors was 2.78 ± 1.32 (cm). Themain type of lesions was detected on ultrasound was local lesion with over 77.08%with an unknown boundary feature (66.67%) and invasive, accounting for 43.75%.Histopathological type accounted for the highest proportion was the invasive tubularcarcinoma (79.92%). Histological degree accounted for the highest percentage wasdegree 2 with 45.83%. Stage II accounted for the highest rate with 39.58%, stage VIhad the lowest rate with 10.42%.Conclusion: Common age of breast cancer patients was 45 - 60 years old, mainlythe self-examined tumor, common breast tumors were found in the upper-externalquadrant. On ultrasound, mainly the local lesion, the boundary was not clear. Thehistopathological type was the invasive tubular carcinoma.
Keywords: Breast cancer, trastuzumab, clinical and subclinical features.